A Critical Discourse Analysis of Selected Utterances of State Actors on the 2019 Xenophobic Attacks on Nigerians in South Africa - Damilola Oluseyi Fafiyebi (Universitas Sanata Dharma, 2020)
The study examined the discourse strategies employed by state actors in expressing their views on the 2019 xenophobic attack in South Africa. The objective is to examine how this group of people explores the provisions of critical discourse to shape and pattern their communicative intention. The data employed for the study were sourced from selected online media sources between September and November 2019. The study employed the Critical Discourse Analysis (CDA) approach with a particular focus on the Discourse Historical Approach framework proposed by Wodak (2001) as its theoretical springboard. The study established that different state actors from each of the countries under scrutiny engage in positive self and negative others presentation. This showed that from their discourses, it can be deduced that the state actors were all out to launder the image of their respective countries on the one hand and that of the kith and kin on the other hand.